Sample size justification in feasibility studies: moving beyond published guidance - Robert Montgomery (Pilot and Feasibility Studies, 2025)
Abstract Pilot and feasibility studies are crucial for determining whether follow-up trials should be conducted. To be effective, these studies need to be properly designed and have large enough samples to make correct decisions about proceeding to a future trial at a high rate. However, there is significantly less clarity about best practices concerning sample size justifications compared to larger randomized controlled trials which are usually justified by power analyses. This has led to many feasibility studies justifying sample sizes based on pragmatic reasons (e.g., the ability to complete) or on published guidance and various rules of thumb. We argue that feasibility studies should be designed for, or at least report relevant operating characteristics, specifically, the probability of determining a future trial will be feasible when it is and the probability of determining a trial will be feasible when it is not and that sample size justifications should be based on these operating characteristics whenever possible. If relevant operating characteristics for a study are not reported, it is difficult to know whether the evidence from these trials can be used to claim a future trial would be feasible. In this paper, we review common methods for determining samples sizes in feasibility studies, report a narrative review of recently published feasibility studies and use two case-studies to highlight core issues we believe exist in the current design and reporting of these studies. Finally, we provide some suggestions that we believe will enhance the sample size justifications and overall effectiveness of these important trials.